POTENSI SIMPANAN KARBON DI ATAS PERMUKAAN TANAH TEGAKAN Acacia nilotica L. (Willd) ex. Del. DI TAMAN NASIONAL BALURAN, JAWA TIMUR - Istomo Istomo; Nur Eliya Farida (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
Acacia nilotica is an invasive species which is difficult to eradicate up to present.  A. nilotica is a fast growing species of savanna tree, and therefore is supposed probably to have relatively high biomass and carbon content.  The objective of this research was to develop allometric equation of biomass and estimating the carbon storage potential in A. nilotica stand in Baluran National Park.   This research used destructive method on 9 sample trees to construct allometric equation. For measuring biomass potency, vegetation analysis was conducted using 3 plots, measuring 100 m x 100 m each on the basis of A nilotica stand density categorization (high, medium, and low).  For obtaining data of carbon potency, biomass value was multiplied with 0,47.  Research results show that the selected allometric equation for tree total is W=0,34 D1,97 with R2of 98,4. Average biomass potency was as large as 25 tons/ha.   Average carbon potency was 11,92 ton/ha.   Management of A. niloticain Baluran National Park, in moderate and low density stand can be in the form of clear cutting, whereas high density stand can be maintained for carbon sequestration and utilization by the people community for supplying seeds, livestock feeds, firewood or charcoal briquette.